2011
DOI: 10.1111/j.1463-1326.2011.01524.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic effects of bariatric surgery in type 2 diabetic patients with body mass index < 35 kg/m2

Abstract: Bariatric surgery is effectual and safe in the treatment of non-severely obese (BMI < 35 kg/m(2) ) T2DM patients. Moreover, the metabolic benefits acquired from the procedures can be long sustained after the surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(40 citation statements)
references
References 37 publications
3
34
1
2
Order By: Relevance
“…In an above-mentioned meta-analysis, a 6.2% major surgical complication rate, including intestinal obstruction, intestinal perforation, and intra-abdominal bleeding, was reported, as well as a 1.7% reoperation rate (19). This rate is much higher than the 3.2% complication rate reported in patients with a somewhat higher BMI (44).…”
contrasting
confidence: 56%
“…In an above-mentioned meta-analysis, a 6.2% major surgical complication rate, including intestinal obstruction, intestinal perforation, and intra-abdominal bleeding, was reported, as well as a 1.7% reoperation rate (19). This rate is much higher than the 3.2% complication rate reported in patients with a somewhat higher BMI (44).…”
contrasting
confidence: 56%
“…However, bariatric surgery is beneficial for cases of class I and II obesity and even overweight when there are associated comorbidities. This is reinforced by investigations on the metabolic effects of bariatric surgery in patients with BMI above 35Kg/m² and type 2 diabetes mellitus revealing that the surgical option is an important therapeutic modality for the control of this disease (11) . The mean length of hospital stay of our patients was 6.3 days.…”
Section: Discussionmentioning
confidence: 97%
“…Lifestyle interventions to prevent T2DM have not avoided cardiovascular events, even with long-term follow-up [36,37]. Sjöström et al [38 •• ], in the Swedish Obese Subjects study, a nonrandomized prospective study, concluded that bariatric surgery led to a reduced number of cardiovascular events and deaths compared with usual care.…”
Section: Balancing the Role Of Weight Loss In T2dm Control And Cardiomentioning
confidence: 99%